Claims Management and Substantiation in the United Arab Emirates Construction Sector - Zubaida, Nael Maher (2012)
Many construction companies operating in the United Arab Emirates face a number of constraints which negatively affect the execution of projects. Such constraints have a direct effect on the cost and time factors of the project. Independent of the constraints perceived, the difficulties in completing projects in a timely manner lead contractors to formulate claims in an effort to maintain their contractual rights and in an attempt to avoid penalties specified in the contracts. This dissertation aimed at developing a claims management system which can be applied by contractors to ensure that their claims were substantiated adequately. To gain a better understanding of claims, types of claims and substantiation were all factors which were reviewed in an attempt to enable contractors to further grasp the knowledge required to establish a well-structured claims management system. This was achieved through developing a conceptual framework which contained all the concepts claims management revolved around. The study was of qualitative nature and the tools used were based on semi-structured interviews and case study approach. The construction company which was referred to as part of the analysis was called ABC. Interviews were held with professionals working in construction organizations and who were directly involved in the claims which surfaced in their projects. The study provided in the conclusion the necessary elements which construction firms need to take into consideration when formulating their claims. The managerial aspect was the focus of the study rather than the legal aspect. Some of the findings revealed in this dissertation were the importance of records keeping, formal notifications and significance of change and change orders in the context of claims management and other key aspects relevant to the field of claims management and substantiation.